PENCATATAN AKAD UTANG PIUTANG UNTUK MEMELIHARA HARTA (HIFDZUL MAL) DALAM KAJIAN HUKUM EKONOMI SYARI’AH - Ahmad Fauzi (MUAMALATUNA, 2021)
Islam is a perfect religion which regulates all aspects of life not only limited to spiritual matters. One of them is the activity of bermuamalah, namely in the activities of accounts payable. Allah instructs humans to keep records when making non-cash transactions, this is so that assets are preserved (hifdzul mal). However, in reality, many people do not keep records, so that there are often misunderstandings and even conflicts. The purpose of this research is to know about 1) Definition of Accounts Receivable in Islamic Economic Law; 2) The Urgency of Recording Accounts Receivable To Maintain Assets (Hifdzul Mal). This type of research is qualitative with the descriptive-analytic method. Sources of data were obtained usingsources library research. The conclusion in this study is that the recording of accounts payable is carried out in order to achieve the benefits of both parties and the realization of the maqashid sharia, namely the maintenance of the assets (hidzul mal) of the parties who carry out the debt and credit transactions.